Fabricação de estruturas ordenadas sobre grafeno usando a alumina porosa como máscara de evaporação - Eduardo Nery Duarte de Araujo (2011)
One of the main challenges of microelectronics in recent years has been producing devices with even nanometric dimensions, without losing the properties and the control of the electrical current. It is known that in 2D electron gas effects such as collimation, focusing and interference are possible through the use of external fields. However, it is difficult to build devices using external fields to control electron propagation. The work of C. H. Park et al. suggest that a modulating potential with a periodicity of the order of nanometers, fabricated on grapheme, would be able to collimate an incident electron beam without the need of a waveguide or external fields. In this work, we demonstrate that the porous alumina can be used as an evaporation mask, to produce a modulating potential superimposed onto graphene. Alumina is particularly useful as evaporation masks since it presents a self- organized network of pores that arise during the anodic oxidation of aluminum, besides its low cost. The alumina pores have diameters and distances between neighbors of the order of tens of nanometers, with a length of the order of micrometers, and these parameters are adjustable.The alumina nanoporous membrane with suitably adjusted parameters to be used as good evaporation mask was applied in the production of a superlattice of Cr/Au nanodots on the graphene. A study was made on the properties of the electrical transport under the modulating potential and was proposed a device to analyze the current distribution on the graphene surface under a periodic metal network.